The effect of ignition timing on engine performance and combustion behaviour of LPG-SI engine using lsi system - Tukiman, Mohd Mustaqim (2022)
Liquefied petroleum gas (LPG) is one of the potential alternative fuels for Spark Ignition (SI) due to its availability and acknowledged superior properties compared to the gasoline. However, implementing the latest generation of LPG on the SI engine, which uses liquid sequential injection (LSI) in the fuel delivery system, needs a detailed analysis of the engine characterization. A series of experiments were performed at various engine speeds from 1500 RPM to 3500 RPM with an increment of 500 RPM and the throttle position (TP) was set at 25%, 50% and 75%. The spark ignition angle was also tested from -5 SI °CA to -35 SI °CA Before Top Dead Centre (BTDC) with the increment of 5 SI °CA and runnings at stoichiometric condition. As a result, the LSI-LPG significantly improved the engine performance in the range between 0.3 % and 12.63% when the spark ignition angle was adjusted at the MBT locations. The Brake Specific Fuel Consumption (BSFC) also improved by about 4.5% to 13.6%. The CO and CO2 from exhaust emissions reduced from 25% to 20%. Besides that, HC and NOX was also reduced by 47% to 47.7 % compared to gasoline at MBT locations. The engine was simulated in actual driving conditions (90 km/h at 3000 RPM).The peak pressure indicated an improvement of 2.4% to 10% at all engine conditions, and the peak location was at 16.6°CA to 18.4°CA After Top Dead Centre (ATDC). The Coefficient of Variation (COV) was also lower than gasoline, ranging from 4.85% to 6.36%, which exhibited better combustion. In addition, the Rate of Pressure Rise (ROPR), Rate of Heat Released (ROHR) and Mass Fraction Burn (MFB) produced from LSI-LPG are better than gasoline when the spark ignition angle was adjusted at the correct location. Therefore, the use of LSI-LPG into the gasoline engine is able to improved engine performance without jeopardize the exhaust emission.